The Effect of Polar Substituents on Dielectric and Optical Transmittance Properties of two λ-shaped Mesogenic with Bromo and Chloro Substituents - A Comparative Study - Chand, PB; Manohar, R (Scientific World, 2010)
Dielectric properties of two λ-shaped mesogenic compounds 4-((2-bromo-4-nitrophenyl)diazenyl)-1,3-phenylene bis(4-(tetradecyloxy)benzoate) (14MV) and 4-((2-chloro-4-nitrophenyl)diazenl)-1,3-phenylene bis(4-(decyloxy)benzoate) (10-OCPNDE) have been studied as a function of temperature and frequency. The bromo substituents compound exhibits smectic C phase but chloro substituents compound smectic A phase. Our interest is to compare the macroscopic properties of the two compounds of same category but different functional group i.e Br or Cl. With this aim, the dielectric permittivity with temperature and frequency has been determined for both the compounds in planar alignment at frequency range 100Hz- 1MHz. In this paper, we reported the dielectric behaviour of the effect of bromo and chloro substituents on mesomorphic two λ-shaped mesogenic homologous series with bromo and chloro substituents. Key words: λ-shaped liquid crystals; Polar substituents; Dielectric properties; Cole-Cole plot. DOI: 10.3126/sw.v8i8.3851 Scientific World Vol.8(8) 2010 pp.59-65